Core Python programming - Chun, Wesley (Prentice Hall PTR core series., 2006)
Praise for Core Python Programming "The long-awaited second edition of Wesley Chun's Core Python Programming proves to be well worth the wait-its deep and broad coverage and useful exercises will help readers learn and practice good Python."--Alex Martelli, author of Python in a Nutshell and editor of Python Cookbook "There has been lot of good buzz around Wesley Chun's Core Python Programming . It turns out that all the buzz is well earned. I think this is the best book currently available for learning Python. I would recommend Chun's book over Learning Python (O'Reilly), Programming Python (O'Reilly), or The Quick Python Book (Manning)." -David Mertz, Ph.D., IBM DeveloperWorks® "I have been doing a lot of research [on] Python for the past year and have seen a number of positive reviews of your book. The sentiment expressed confirms the opinion that Core Python Programming is now considered the standard introductory text." -Richard Ozaki, Lockheed Martin "Finally, a book good enough to be both a textbook and a reference on the Python language now exists." -Michael Baxter, Linux Journal "Very well written. It is the clearest, friendliest book I have come across yet for explaining Python, and putting it in a wider context. It does not presume a large amount of other experience. It does go into some important Python topics carefully and in depth. Unlike too many beginner books, it never condescends or tortures the reader with childish hide-and-seek prose games. [It] sticks to gaining a solid grasp of Python syntax and structure." -http://python.org bookstore Web site "[If] I could only own one Python book, it would be Core Python Programming by Wesley Chun. This book manages to cover more topics in more depth than Learning Python but includes it all in one book that also more than adequately covers the core language. [If] you are in the market for just one book about Python, I recommend this book. You will enjoy reading it, including its wry programmer's wit. More importantly, you will learn Python. Even more importantly, you will find it invaluable in helping you in your day-to-day Python programming life. Well done, Mr. Chun!" -Ron Stephens, Python Learning Foundation "I think the best language for beginners is Python, without a doubt. My favorite book is Core Python Programming ." -s003apr, MP3Car.com Forums "Personally, I really like Python. It's simple to learn, completely intuitive, amazingly flexible, and pretty darned fast. Python has o ...